2006
DOI: 10.1055/s-2006-951723
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical and Pharmacological Characterization of a New Oleogel-Forming Triterpene Extract from the Outer Bark of Birch (Betulae Cortex)

Abstract: Triterpenes are biologically active secondary plant substances that display antimicrobial, hepatoprotective and anti-inflammatory effects. However, the poor solubility of triterpenes in both polar and non-polar solvents as well as expensive purification procedures have prevented the large-scale isolation of these compounds for medicinal purposes. Here, we describe a novel quantitative extraction method of triterpenes from the outer bark of birch (Betula species) in which betulin, a lupan triterpene, predominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 18 publications
0
97
0
2
Order By: Relevance
“…Due to the radical scavenging potential of these phytochemicals, toxicity level reduces and body tends back towards normalcy (Laszczyk et al, 2006). Several studies have shown the hepatoprotective effects of Justicia leaves (Pandit et al, 2004;Bhattacharya et al, 2005;Krishna et al, 2010), but no work has reported on flowers of J. adhatoda.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the radical scavenging potential of these phytochemicals, toxicity level reduces and body tends back towards normalcy (Laszczyk et al, 2006). Several studies have shown the hepatoprotective effects of Justicia leaves (Pandit et al, 2004;Bhattacharya et al, 2005;Krishna et al, 2010), but no work has reported on flowers of J. adhatoda.…”
Section: Discussionmentioning
confidence: 99%
“…antibacterial, antiviral, anti-parasite BE: [5,6]; BA: [7][8][9]; BE/BA: [10,11]; BE/BA/OA: [12]; LU/BA: [13]; OA/BA: [14] hepatoprotective BE: [15]; BE/BA: [16]; OA: [17][18][19][20]; LU: [21]; BA: [22] antitumor BE: [23,24]; BA: [25,26] BE/BA: [27,28]; LU: [29]; OA: [18,19,30] wound healing extract: [31][32][33]; BA: [34]; OA: [35,36] anti-inflammatory BE: [5,37]; LU: [38,39]; OA: [18,40] Apart from these pharmacological effects, birch bark extract is able to act as a gelling agent and Pickering emulsifier [41][42][43]. Together with its anti-inflammatory and wound healing effects, this makes birch bark dry extract interesting for the stabilisation of semisolid systems, such as gels and creams, acting as an active ingredient and an excipient in parallel.…”
Section: Pharmacological Effects Of Triterpenoids Contained In Birch mentioning
confidence: 99%
“…They can be extracted as a triterpene rich dry extract (TE) which is able to form a topically applicable oleogel [1,2]. The birch triterpenes have known antiviral, antimicrobial and hepatoprotective pharmacological activities [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The birch triterpenes have known antiviral, antimicrobial and hepatoprotective pharmacological activities [3][4][5]. BA, OA or BE also have antitumor effects [2,6,7]. These triterpenes show antiinflammatory activities, as do others such as ER or LU [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%